1987
DOI: 10.1016/0014-5793(87)80508-2
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP induces Ca2+ transients in cardiac myocytes which are potentiated by norepinephrine

Abstract: Isolated rat ventricular cardiac myocytes loaded with the fluorescent calcium indicator fura2 Showed significant changes in intracellular calcium concentrations upon exposure to > 1/tM ATP (ECs0 = 7.4_ 1.3 gM, n =4, SE), suggesting that extracellular ATP may have an important influence on myocardial contractility. The response was found to be highly ATP specific and required extracellular calcium. Furthermore, 30 s pretreatment of the cells with 0.2-1 #M norepinephrine decreased the concentration of ATP requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…More generally, ATP may be released simultaneously with noradrenaline or acetylcholine since several neurochemical studies suggest that single neurones may contain and release more than one active compound (Lundberg, Terenius, Hokfelt & Goldstein, 1983). Thus, ATP should be considered as a neurotransmitter in the mammal as well as in the frog heart (Hoyle & Burnstock, 1986) and may act in concert with other agonists to regulate myocardial calcium homeostasis (De Young & Scarpa, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, ATP may be released simultaneously with noradrenaline or acetylcholine since several neurochemical studies suggest that single neurones may contain and release more than one active compound (Lundberg, Terenius, Hokfelt & Goldstein, 1983). Thus, ATP should be considered as a neurotransmitter in the mammal as well as in the frog heart (Hoyle & Burnstock, 1986) and may act in concert with other agonists to regulate myocardial calcium homeostasis (De Young & Scarpa, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of [Ca2 li Ventricular myocytes were prepared from 200-250g male Sprague-Dawley rats according to the method described previously (Young & Scarpa, 1987;Huang & Wong, 1991) with slight modifications. In brief, the heart was mounted on a modified Langendorff perfusion apparatus and perfused at 10 ml min ' with oxygenated Joklik modified Eagles medium supplemented with 1.25 mM CaCI2 and 10 mM HEPES, pH 7.2, at 37C for 5 min followed by 5 min in the same medium without calcium.…”
Section: Rabbit Sinoatrial Nodementioning
confidence: 99%
“…In the rat ventricular myocytes, previous reports show an increase in [Ca2+]i by an application of ATP (Danziger et'al., 1988;Bjornsson et al, 1989;de Young & Scarpa, 1987 ponses for both intracellular acidification (Puceat et al, 1991b) and extracellular phosphorylation (Christie et al, 1992) were observed at 60 s after the ATP application. Thus,…”
Section: Concentration-response Relationship Of Iatpsmentioning
confidence: 99%